Influence of margin location and luting material on the amount of undetected cement excess on CAD/CAM implant abutments and cement-retained zirconia crowns: an in-vitro study - Peter Gehrke; Konstantin Bleuel; Carsten Fischer; Robert Sader (BMC, 2019)
Abstract Background The flexibility in designing the submucosal part of CAD/CAM customized implant abutments and the individual positioning of its shoulder line has been suggested to reduce the risk of leaving undetected cement residues, thus preventing adverse effects on peri-implant tissues. A high correlation between excess cement left in the soft tissues and the occurrence of increased biofilm accumulation with sulcular bleeding and/ or suppuration has been reported. This in turn may cause peri-implant inflammation and peri-implant marginal bone loss. The aim of this study was to assess the frequency of cement remnants after the luting of zirconia crowns on CAD/CAM custom molar abutments with different margin levels and to evaluate the impact of the luting material. Material and methods A total of 20 titanium molar CAD/CAM implant abutments (BEGO Medical GmbH) with internal taper connection/ internal hex anti-rotation protection, and a convex emergence profile with different margin positions (0, 1, 2 and 3 mm below the mucosa), were virtually designed (Implant Studio, 3Shape) and manufactured. A master cast was scanned, duplicated by a 3D printer and individual gingival masks were produced to simulate peri-implant soft tissues. 20 corresponding zirconia crowns were designed (Cerec 3D, Dentsply Sirona), produced and cemented to the abutments with two different luting materials; a zinc oxide non-eugenol cement (Temp Bond NE) or a methacrylate cement (Panavia V5). To ensure retrievability of the crown/abutment connection, occlusal openings providing access to the abutment screws were designed. Excess cement was thoroughly removed and the crown/abutment units were unscrewed to evaluate the occurrence of cement residues. All the quadrants of each specimen were evaluated for calculation of the ratio between the cement remnant area and the total specimen area using Adobe Photoshop. Spearman analysis was performed to detect correlations between different variables. A two-sided t-test, ANOVA, Mann-Whitney, and Kruskal-Wallis tests were applied to detect differences between the groups. Results Cement remnants were found in every depth of the crown abutment complex and in almost every area investigated. The amount of cement residues increased as the crown-abutment margin was located more submucosally. Lingual areas were more prone to cement remnants than other surface areas (p = 0.0291). Excess cement was not only found at the margins of the crown-abutment complex, but also underneath (basal) the abutment itself, where cleaning was impossible. No statistical difference in the effect of zinc oxide non-eugenol- and methacrylate cement on the frequency of excess material at the lateral abutment surfaces could be demonstrated in vitro. The proportion of basal abutment aspects covered with cement residues was, however, significantly smaller in Panavia V5 samples with an average of 4.9 ± 3.7% compared to Temp Bond samples with an average of 8.6 ± 5.5%. Conclusions Given the results obtained in the present investigation the margin of CAD/CAM molar abutments should be located as coronally as possible to minimize the amount of cement remnants. If an epigingival or supragingival margin location is not feasible due to esthetic concerns, it cannot be recommended to place the margin of molar CAD/CAM abutments deeper than 1.5 mm in the proximal and oral regions.